Vessels of wrath - Blaylock, Richard M. (Pickwick Publications, 2023)
Hardening hearts. Blinding eyes. Sending deceitful spirits. Crafting vessels of wrath. Few will deny that certain biblical passages make claims about God that are difficult to accept. But perhaps the most troubling are the verses that describe God as influencing individuals or groups towards wicked behavior for the purpose of condemning them. What are readers to do with these texts? In Vessels of Wrath, Richard M. Blaylock tackles the thorny subject of divine reprobating activity (DRA). Through an exhaustive, biblical-theological study of the Old and New Testaments, Blaylock argues that the Bible does not present DRA as an insignificant or monolithic concept; instead, the biblical authors showcase both the significance and the complexity of DRA in a variety of ways. The book aims to help readers of the Bible to wrestle with the Scriptures so that they might come to better understand its testimony to this mysterious and awesome divine activity